Discrepancy Evaluation of 10 Antenatal Care Services (10T) at the Dinoyo Health Center, Malang City - Orin, Yosefina Salestina; Wardani, Hartati Eko; Ekawati, Rany; Hapsari, Anindya (Preventia: The Indonesian Journal of Public Health, 2023)
One of the goals of the Antenatal Care (ANC) program is to identify abnormalities or complications early that may occur during pregnancy. The quality of antenatal care contributes to better outcomes for pregnant women. Meanwhile, at the Dinoyo Health Center, the coverage of antenatal care visits showed a decreased trend. Furthermore, the quality of ten antenatal care services (10T) was still unknown. This study aimed to evaluate the implementation of ten antenatal care services (10T) at the Dinoyo Health Center. This descriptive qualitative study was conducted at the Dinoyo Health Center on April 2022. Data were obtained from ten informants that were purposively selected and also from secondary data. Data analysis was carried out using the Discrepancy Evaluation Model (DEM) approach. The data triangulation process was also done. This study found that one of ten antenatal care services (10T) did not meet the standard. It was a counseling session.